Facial expression recognition application system - Chan, Marisabel B. (2002)
Previous attempts on facial expression recognition use the Facial Action Coding System (FACS) which charts every possible facial muscle action to categorize emotions. This is an exhaustive approach and we resorted to simpler methods. Presented is the Facial Expression Recognition Application System (FERAS) employing the facetrain package by Jeff Shufelt of the Carnegie Mellon University. Our system implements a backpropagation algorithm for neural networks. Given a 90 by 100 pixel PGM images as inputs, the recognizer utilizes a three-layer, fully-connected, feed-forward approach to classify the facial expression displayed as to whether it is happy, sad or surprised. FERAS is applied to control and enhance a child tutorial system.